2003
DOI: 10.1021/jo034334t
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of the Nonproteinogenic Amino Acid (2S,3R)-3-Amino-2-hydroxydecanoic Acid from (4S,5S)-4-Formyl-5-vinyl-2-oxazolidinone

Abstract: (4S,5S)-4-Formyl-5-vinyl-2-oxazolidinone (4b), which is readily obtained via a zinc-silver-mediated reductive elimination of alpha-d-lyxofuranosyl phenyl sulfone (3b), is successfully converted to the naturally occurring, nonproteinogenic amino acid (2S,3R)-3-amino-2-hydroxydecanoic acid (2). Also in this study, a facile "oxazolidinone rearrangement" reaction is uncovered during the attempted formation of the (methylthio)thiocarbonate derivative of the oxazolidinone alcohol 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The spectral and analytical data of 2a was found to be in good agreement with published data ([α] D 25 +5.6 ( c 0.51, 1 M HCl). [α] D 22 +7.3 ( c 0.37, 1 M HCl)) [18]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral and analytical data of 2a was found to be in good agreement with published data ([α] D 25 +5.6 ( c 0.51, 1 M HCl). [α] D 22 +7.3 ( c 0.37, 1 M HCl)) [18]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, a few strategies employ a chiral pool approach. For example, Wee et al utilized the zinc-silver-mediated reductive elimination of α-D-lyxofuranosyl phenylsulfone to get (4 S ,5 S )-4-formyl-5-vinyl-2-oxazolidone, which was converted into 2a [18]. Merrer and co-workers used D-isoascorbic acid, which was transformed via (2 R )-amino-1,3,4-triol to 2a [19].…”
Section: Introductionmentioning
confidence: 99%
“…The intense interesting in this field and one of the major goals of crystal engineering are targeted at predictable assembly of molecular species into extended architectures, and the potential applications, such as biological assays, catalysis, porosity, magnetism, light-emitting diodes and optical fibers for telecommunications [6][7][8][9], among which, later transition metal ions such as nickel, zinc, cadmium, silver are found to adopt a wide variety of geometries and exhibit interesting physical property [10][11][12][13][14][15][16]. Flexible ligands, especially, those N, O, S -containing donors possess rich structural information [17].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The O,N-containing five-membered ring motif is also a versatile building block and ligand in organic synthesis. [2] For this reason, the development of catalytic methods for their facile assembly with selective control of substitution patterns continues to be actively pursued. [1][2][3] In recent years, an increasing number of studies have demonstrated the versatility of π-rich alcohols as substrates in Brønsted acid-catalyzed carbon-carbon bond formation methods.…”
mentioning
confidence: 99%
“…[2] For this reason, the development of catalytic methods for their facile assembly with selective control of substitution patterns continues to be actively pursued. [1][2][3] In recent years, an increasing number of studies have demonstrated the versatility of π-rich alcohols as substrates in Brønsted acid-catalyzed carbon-carbon bond formation methods. [4][5][6] This has included efforts by us and others to shepherd the putative carbocationic species, generated under such reaction conditions, to participate in cyclization pathways to afford cyclic products of potential synthetic value.…”
mentioning
confidence: 99%